Ochratoxin A and Sterigmatocystin in Long-Ripened Grana Cheese: Occurrence, Wheel Rind Contamination and Effectiveness of Cleaning Techniques on Grated Products - Amedeo Pietri; Giulia Leni; Annalisa Mulazzi; Terenzio Bertuzzi (Toxins, 2022)
A survey on the occurrence of ochratoxin A (OTA) and sterigmatocystin (STC) in grated cheese products obtained from hard grana-type cheeses was carried out, where 107 grated products were collected in retail outlets and analysed. OTA and STC were found in 48.6% and 94.4% of the samples, in a range from <LOD to 25.05 µg kg−1 and from <LOD to 6.87 µg kg−1, respectively. STC was detected in all the OTA-contaminated samples. The OTA and STC occurrence in cheese is due to environmental contamination during ripening, leading to fungal growth and mycotoxin production on the cheese surface. This statement was confirmed by analysing the surface of 16 hard grana cheese rinds, which resulted contaminated by both OTA and STC, with concentration ranging from 3 to 370 µg kg−1. This finding demonstrates that rind inclusion increases the mycotoxin concentration in grated cheeses. The mycotoxin level significantly decreased from the surface (0–1.5 mm) to inner parts of cheese rinds (1.5–4.5 mm). Industrial wheel-cleaning techniques can represent a useful treatment to reduce both toxins in grated cheese products.